2018
DOI: 10.1007/s10653-018-0129-5
|View full text |Cite
|
Sign up to set email alerts
|

Histamine-binding capacities of different natural zeolites: a comparative study

Abstract: Two different natural zeolites from Cuba and Mexico, which are already being used as contemporaneous drugs or dietary supplements in Germany and Mexico, respectively, are applied in a comparative study of their histamine-binding capacities as a function of their particle sizes. The zeolites are characterized using X-ray diffraction (XRD), scanning electron microscopy (SEM) and N-sorption measurements (BET surface areas). The Cuban zeolite contains clinoptilolite and mordenite as major phases (78% zeolite), whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Clinoptilolite is the most abundant phase, followed by mordenite, and the two zeolites constitute 68.2 ± 5.5% by weight of the material. The amounts of clinoptilolite and mordenite determined in this sample are similar to those reported earlier by Selvam et al ( 2014 , 2018 ) obtained through a semi-quantitative analysis of the same material. Feldspars, chlorite, tridymite, and smectite represent minor components, whereas the amount of amorphous fraction, constituted by volcanic glass, is significant (Table 1 ); the comparison between observed and calculated X-ray diffraction (XRD) patterns is reported in Electronic Supplementary Material.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Clinoptilolite is the most abundant phase, followed by mordenite, and the two zeolites constitute 68.2 ± 5.5% by weight of the material. The amounts of clinoptilolite and mordenite determined in this sample are similar to those reported earlier by Selvam et al ( 2014 , 2018 ) obtained through a semi-quantitative analysis of the same material. Feldspars, chlorite, tridymite, and smectite represent minor components, whereas the amount of amorphous fraction, constituted by volcanic glass, is significant (Table 1 ); the comparison between observed and calculated X-ray diffraction (XRD) patterns is reported in Electronic Supplementary Material.…”
Section: Resultssupporting
confidence: 91%
“…Based on the above considerations, the present work investigates the effects on H. pylori growth of a zeolite-bearing Cuban material, which has been evaluated in its natural form, as well as in its Na- and Zn-exchanged counterparts. The material used for this research is mainly composed of two zeolites, clinoptilolite and mordenite, is known for its high adsorption capacity for histamine (Selvam et al 2014 , 2018 ), and is already used as medical device in various oral and topical applications (Langbein et al 2019 ; Torres et al 2019 ; Dathe 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For some inorganic minerals, such as zeolite, it was reported that the larger external clay BET surface area and pore volume might speed up the blood coagulation, because of its correspondingly increased water absorption, which concentrated the blood and accelerated the coagulation [12,14,40]. Zeolites exhibit high BET surface areas (98–119 m 2 /g) and high total pore volumes (0.19–0.220 cm 3 /g) [41], which in turn can rapidly absorb water at the site of bleeding in a nonchemical reaction, effectively concentrating the platelets and clotting factors to promote coagulation [12]. These results further confirmed that the main hemostatic mechanism of kaolinite does not rely on water absorption to concentrate blood, which is different from zeolite [11].…”
Section: Discussionmentioning
confidence: 99%
“…Whether the serotonin level decrease in 6 patients is based on the adsorption of serotonin by the zeolite – similar to the histamine uptake – or the decline of the chemically-labile serotonin is caused by other mechanisms is still the subject of ongoing investigations[18,19]. Nevertheless, these 6 patients were part of the satisfied ones with respect to the bowel movements (Table 2) corresponding to correlation of serotonin level and diarrhea[3-5].…”
Section: Discussionmentioning
confidence: 99%
“…This kind of treatment differs significantly from all other drugs in the field because Detoxsan ® powder acts only via its inherent adsorption properties within the gastrointestinal tract; neither does it penetrate into the blood circulation nor directly influence regulation processes. Furthermore, it is noteworthy that the histamine uptake of the Cuban zeolite (and possibly of other biogenic amines) is significantly higher compared to other zeolites containing only clinoptilolite and no additional mordenite[19]. The clinical treatment of patients with NETs with regard to their functional complaints is recently focused to the application of somatostatin receptor inhibitors[36].…”
Section: Discussionmentioning
confidence: 99%